Industrial training final report : Perunding Alif Bersatu Sdn. Bhd. / Muhammad Amirul Shafiq Shaiful - Shaiful, Muhammad Amirul Shafiq (Universiti Teknologi MARA, Pulau Pinang, 2024)
Perunding Alif Bersatu Sdn. Bhd., established on July 3, 2003, is a leading engineering consultancy firm based in Shah Alam, Selangor, Malaysia. Specializing in Mechanical and Electrical Engineering as well as Project Management Consultancy, the company has built a strong reputation for providing innovative and high-quality solutions to both private and public sector clients. With over two decades of experience, the firm has successfully delivered projects in various industries, including residential, commercial, industrial, and infrastructure developments, ensuring adherence to local and international standards. The company is driven by a dedicated team of professionals, including six skilled engineers, one accountant, one administrative staff, and five CAD operators. This talented team works collaboratively to provide tailored engineering designs and project management services that focus on sustainability, efficiency, and cost- effectiveness. Perunding Alif Bersatu Sdn. Bhd. prides itself on its ability to offer cutting-edge solutions, whether in the design of mechanical and electrical systems or in overseeing the execution of complex projects from start to finish, ensuring they are completed on time and within budget.